Assessing Measurement Invariance of Achievement Emotions Questionnaire for Teachers in Prospective Teacher Sample - Sevilay Kilmen (International Journal of Assessment Tools in Education)
The purpose of the current study is to determine whether the Achievement Emotions Questionnaire for Teachers (AEQT) is a psychometrically sound instrument to measure prospective teachers' teaching-related emotions. The three-factor model of the AEQT was confirmed in a prospective teacher sample. Also, reliability results showed that the AEQT is a reliable measurement tool. Measurement invariance results revealed that configural, metric, and scalar invariance were provided across gender. These findings support the use of the AEQT when examining differences based on achievement emotions across gender. For teacher training programs, only configural invariance was provided. Although configural invariance suggests that the three-factor structure of the AEQT is the same across the teacher training programs, the lack of metric invariance indicates that the relationship between the items and the underlying latent variable the AEQT factors is not the same across these groups. The observed variables are not related to the latent variable equivalently across teacher training programs. This result does not allow the comparison of path coefficients and covariances between observed and latent variables across teacher training programs. Also, the lack of scalar invariance indicates that different teacher training programs may interpret some items differently and prevent a comparison of averages between these groups.